1980
DOI: 10.1002/ar.1091960106
|View full text |Cite
|
Sign up to set email alerts
|

The origin of the extrinsic adrenergic innervation to the rat ovary

Abstract: Cutting the suspensory ligament reduced the ovarian content of norepinephrine (NE) to less than half that of controls and only a few blood vessels had perivascular fibers and an occasional nerve remained in the interstitial gland. Cutting the ovarian plexus had a less drastic, but similar effect on the ovarian content of NE and on the pattern of ovarian adrenergic nerves. Cutting both the suspensory ligament and ovarian plexus eliminated visualization of ovarian adrenergic nerves, but some ovarian NE was still… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
142
1

Year Published

1985
1985
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 189 publications
(153 citation statements)
references
References 13 publications
3
142
1
Order By: Relevance
“…Both hormones provide a microenvironment adequate for the advance of pregnancy (Gibori 1993). Their synthesis is regulated by the hypophysial gonadotropins and modulated by placental factors (Rothchild 1981) among others (Villavicencio et al 2002) and the neural effect mainly caused by the superior ovarian nerve (SON) (Lawrence & Burden 1980, D'Albora et al 2000, Aguado 2002. Using different experimental schemes, we have demonstrated that the SON modifies the liberation of ovarian steroids in different stages of life in rats (De Bortoli et al 2000, Sosa et al 2000, Casais et al 2001, 2006, Forneris & Aguado 2002.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Both hormones provide a microenvironment adequate for the advance of pregnancy (Gibori 1993). Their synthesis is regulated by the hypophysial gonadotropins and modulated by placental factors (Rothchild 1981) among others (Villavicencio et al 2002) and the neural effect mainly caused by the superior ovarian nerve (SON) (Lawrence & Burden 1980, D'Albora et al 2000, Aguado 2002. Using different experimental schemes, we have demonstrated that the SON modifies the liberation of ovarian steroids in different stages of life in rats (De Bortoli et al 2000, Sosa et al 2000, Casais et al 2001, 2006, Forneris & Aguado 2002.…”
Section: Introductionmentioning
confidence: 81%
“…Most of the fibers that constitute the SON derive from main neurons of the celiac ganglion which is a component of the prevertebral ganglion chain and it is a modulation center in the pathway of the afferent and efferent fibers between the central nervous system and the ovary (Baljet & Drukker 1979, Lawrence & Burden 1980, Klein & Burden 1988.…”
Section: Introductionmentioning
confidence: 99%
“…The procedure was described in previous reports (Lawrence & Burden 1980, Aguado & Ojeda 1984b. Briefly, before ovarian vein cannulation was completed, the suspensory ligament that contains the left SON was isolated by passing a suture thread under it.…”
Section: Son Transectionmentioning
confidence: 99%
“…The rat ovary receives innervation from two main sources: the ovarian plexus nerve that travels along the ovarian artery, and the superior ovarian nerve (SON) which is associated with the suspensory ligament (Lawrence & Burden 1980, Burden 1985. Microscopical studies show the SON fibres innervating thecal and interstitial cells, and also fibres coming from the ovarian plexus nerve associated with the vascular ovarian system (Baljet & Drukker 1980, Burden 1985.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the increasingly recognized influence of the ovary innervation in the control of the diverse organ functions in different reproductive states (Aguado & Ojeda 1984, Sosa et al 2000, Casais et al 2001, Garraza et al 2004, and the participation of NO in steroidogenesis, as observed in prepubertal rats , and also in the biochemical and vascular changes that occur in the ovulating period, development and regression of the corpus luteum (Acosta & Miyamoto 2004), we also thought it could be interesting to study the neural influence of the superior mesenteric ganglion on the NO ovarian liberation during oestrus. The oestrus is the stage of the oestrous cycle when there is more ovarian irrigation (Acosta & Miyamoto 2004), and the nervous plexus is related with the blood flow (Lawrence & Burden 1980). With this purpose in mind, this work intends (1) to standardize an integrated ex vivo superior mesenteric ganglion-ONP-ovary system in oestrus day rats; (2) to determine if the ganglion cholinergic stimulus modifies the release of nitric oxide and steroids in the ovary compartment in the absence of humoral factors; and (3) to investigate if there are differences in the responses between the left and right ovaries caused by the neural stimulus.…”
Section: Introductionmentioning
confidence: 99%